Cutaneous leishmaniasis in Syria: clinical features, current status and the effects of war - Hayani, Kinan; Dandashli, Anwar; Weisshaar, Elke (Acta dermato-venereologica, 2015)
Cutaneous leishmaniasis (CL) is a worldwide disease caused by an infection with the protozoan parasi...
Epub ahead of print Oct 24, 2014
Gesehen am 16.07.2020